The Effect of Capital Structure and Time Interest Earned Ratio on Profitability: Case Study of the Five Largest Banks in Indonesia for the Period 2020-2023 - Nesa Karondeng; Aida Nafiza Kumalasari; Ronia Tambunan (CAKRAWALA : Management Science Journal, 2024)
This study aims to analyse the effect of Capital Structure and Time Interest Earned (TIE) Ratio on Profitability, a case study of the five largest banks in Indonesia during the 2020-2023 period. The research method used is quantitative research with a multiple linear regression approach. The data used in this study are secondary data from the bank's annual financial statements through the website www.idx.co.id. The independent variable in this study is Capital Structure measured by Debt to Equity Ratio (DER) and Time Interest Earned (TIE) Ratio, while the dependent variable is Profitability measured by Return on Assets (ROA). The results showed that Capital Structure has no positive influence on Profitability and Time Interest Earned Ratio has a positive influence on bank Profitability. Higher capital structure tends to have less effect with lower profitability, while higher Time Interest Earned Ratio is associated with increased profitability. The population in this study are the five largest banks in Indonesia for the period 2020 - 2023. Sampling using saturated sampling technique